Bird Ringing Centre in Sweden (NRM) - Johan Lind (Swedish Museum of Natural History, 2011)
This database contains information about bird ringing in Sweden.
Keywords: Occurrence; Occurrence; Observation; OCCURRENCE; Biological Sciences; Biologi